A qualitative analysis of Medicaid beneficiaries perceptions of prenatal and immediate postpartum contraception counseling. (September 2022) - Yates, Lindsey; Birken, Sarah; Thompson, Terri-Ann; Stuart, Gretchen S; Greene, Sandra; Hassmiller Lich, Kristen; Weinberger, Morris
Objectives: In the United States, about four out of every ten births are financed by Medicaid, making it a program that is key in addressing racial disparities in maternal health. Many women covered by Medicaid have access to prenatal and immediate postpartum contraception counseling that can aid them in their postpartum contraception decision-making. However, existing inequities within Medicaid and a history of reproductive harms targeting Black women and women with low incomes may contribute to women with Medicaid having different experiences of contraception counseling. This qualitative study explores how Black women and White women insured by Medicaid perceive prenatal and immediate postpartum contraception counseling and identifies additional factors that shape their contraception decision-making. Methods: We conducted semi-structured interviews with 15 Medicaid beneficiaries who delivered at a public teaching hospital in North Carolina. Interviews focused on women's beliefs about planning for pregnancy, experiences with prenatal and immediate postpartum contraception counseling, and perceived need for postpartum contraception. We used a priori and emergent codes to analyze interviews. Results: Seven Black women and eight White women completed interviews 14–60 days postpartum. All women reported receiving prenatal and immediate postpartum counseling. Several women described receiving prenatal counseling, reflective of patient-centered contraception counseling, that helped in their postpartum contraception decision-making; one woman described receiving immediate postpartum counseling that helped in her decision-making. Some Black women reported receiving unsupportive/coercive contraception counseling. In addition to contraception counseling, past reproductive health experiences and future pregnancy intentions were salient to women's contraception decision-making. Conclusions: Prenatal and immediate postpartum contraception counseling can help some Medicaid beneficiaries with their postpartum contraception decision, but past reproductive health experiences and future pregnancy intentions are also relevant. Counseling that does not consider these experiences may be harmful, particularly to Black women, further contributing to racial disparities in maternal postpartum health outcomes.